Fibromuscular Dysplasia: Renal Artery Dissection and Infarction in a Young Male - Bdiwi, Mustafa; Dayco, John; Uddin , Mohammed; Afonso, Luis (Clinical and Research Journal in Internal Medicine, 2024)
Fibromuscular dysplasia is an abnormal cell growth of the arterial wall that usually affects the renal and carotid arteries. It may lead to stenosis, tortuosity, aneurysm, or dissection of the artery and can potentially compromise the circulation from ensuing total occlusion and infarction of the recipient area. We report a case of a young male who presented with severe acute abdominal pain in the right side of the abdomen associated with nausea, vomiting, and constipation. Computed tomography of the abdomen with intravenous contrast showed acute renal infarction of a focal area at the lower pole of the right kidney, subsequent computed angiography showed dissection of a segmental branch of the right renal artery associated with fibromuscular dysplasia and beading appearance of the right renal artery. The renal function test and urinalysis were both normal. The patient was treated with unfractionated heparin infusion, with the resolution of abdominal pain, he was subsequently discharged home uneventfully on oral aspirin.